(untitled) (Revista História & Perspectivas, 2010)
A Este artigo discute as maneiras como trabalhadores se movimentam nos espaços sociais. A preocupação central é refletir sobre as práticas sociais e experiências de trabalhadores, colocando em foco as memórias por eles elaboradas ao participarem de processos de transformação. O tema é abordado a partir da perspectiva da história social e por meio de fontes orais. PALAVRAS-CHAVE: Workers. Social practices. Oral narratives. ABSTRACT: This article speak about the way as workers move in a social spaces. The central intention is to reflect about social practices and experiences of workers. Anyway put in focus the memories elaborated by workers when participate of the transformations processes. The theme is approached through of the social history perspective and through oral narratives. KEYWORDS: Workers. Social practices. Oral narratives.